Interaction flow method for many-fermion systems - Honerkamp, Carsten; Enss, Tilman (Arxiv, 2004)
We propose an interaction flow scheme that sums up the perturbation expansion of many-particle systems by successively increasing the interaction strength. It combines the unbiasedness of renormalization group methods with the simplicity of straight-forward perturbation theory. Applying the scheme to fermions in one dimension and to the two-dimensional Hubbard model we find that at one-loop level and low temperatures there is ample agreement with previous one-loop renormalization group approaches. We furthermore present results for the momentum-dependence of spin, charge and pairing interactions in the two-dimensional Hubbard model.